REPRESENTATION OF MULTICULTURAL VALUE IN LISTENING TEXTBOOK USED BY UINSI - Prafitri, Wilma; Nasir, Muhammad Alim Akbar (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
Numerous consequences on East Borneo's multicultural environment will result from the New Capital Country's presence there. Because Indonesia is a cosmopolitan nation with a diversified background, it is crucial to learn multicultural principles there. Thus, including intercultural ideals in textbooks is advantageous. Both the culture of Indonesia and the cultures of other nations must be represented in EFL textbooks. The fact that an EFL textbook is one of the resources students might utilize to learn about the outside world should cause worry. Higher education ought to have featured more cultural representation. In this study, the multicultural ideals portrayed in the listening textbook used at UINSI Samarinda are to be examined. Utilizing the content analysis method, the researcher conducts qualitative research. Klaus (2004) asserts that reliable data references from content are the main emphasis of content analysis. The researcher employed Yuen's (2011) theory, which included the Big C, Little C, perspective, and person categories, to analyze multicultural values. After analysing the data, the researcher found that Little C was the category that was most prevalent in this listening textbook because it portrays cultural practices such as people's daily lives, such as their attire, cuisine, tools, and so on. It may also depend on how people act and how they live their life.